Application research of optical communication network based on artificial intelligence technique - Gangxiang SHEN (Tongxin xuebao)
The applications of artificial intelligence (AI) technique in optical communication networks were explored.Some representative AI applications and potential risks due to the failure of the AI technique were discussed.To address these risks,methods including systematic AI modeling through unitizing and miniaturizing sub-systems and cooperation with traditional network modeling and planning methods were proposed,which were expected to help improve the effectiveness and practicality of the application of the AI technique.Finally,to recover a system from the failure of its employed AI technique or attacks,some protection strategies were proposed.